Efforts to Improve Mathematics Learning Outcomes on Fractional Material by Using a Jigsaw-Type Cooperative Learning Model - Antonius Broto Wahyono; A Rasul; Densemina Y Wadaron (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The low learning outcomes of students in mathematics subjects of fractional material for class VII of SMP Negeri Mapar Mimika, are behind this study. The research method used is Classroom Action Research with the Kemmis and Taggart models which have been implemented for two cycles. Each cycle consists of planning, action, observation and reflection. The subjects of this study were grade VII students of SMP Negeri Mapar Mimika. Data collection techniques consist of observation, observation, documentation, and learning outcomes tests. The research instrument consists of teacher activity sheets, student activity sheets and learning outcomes tests. The results showed that: 1) Efforts to improve student learning outcomes after using the jigsaw-type cooperative learning model in Cycle I obtained an average score of 64.3 percent with a percentage of 60 percent, when carried out in cycle II so that it experienced an average increase in grades of 71.3 percent with a percentage of success of 80 percent, 2) The jigsaw-type cooperative learning model runs optimally, as evidenced by the results of the first cycle of student activity by 70 percent (enough). Increased to 76 percent (good) in cycle II. The results of teacher activity in the first cycle were 66 percent (sufficient), increased to 77 percent (good) in cycle II.